The effect of methyl eugenol from Ocimum minimum on the sticky trap to the direction and daily activity of fruit flies (Bactrocera spp.) - Agus Kardinan; Paramita Maris (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
The fruit fly Bactrocera spp. is a major pest in the horticulture. It caused several important commodities to rot and fall which lead into large loss, or even crop failure. The research objective was to obtain information regarding the activity of fruit fly during night and day and the most attractive direction of sticky trap to trap the fruit flies. The research consisted of 3 activities, namely (1) analysis of active ingredient of Ocimum plant, (2) study on the effect of ocimum sticky traps on the direction of fruit flies, and (3) study on the effect ocimum sticky traps on the daily activity of fruit flies. The study on the effect of time and direction of trap consisted of 4 treatments (North, South, East and West) and 6 replications. A sticky trap contained methyl eugenol as active ingredient, smeared on a yellow plastic surface measuring 10 × 20 cm and attached to 2 m high wooden poles, each facing East and West, as well as North and South (as opposed to one wood). Observations were made every hour starting from 03:00 am to 07:00 pm (until there was no fruit flies get trapped in each treatment). The results showed that sticky trap used contain Ocimum oil containing 76% of methyl eugenol used as an attractant for fruit flies. Fruit flies active during the day where the highest/peak activity of the fruit flies population occured at around 07:00 am. The direction of trap to East and West catched more fruit flies number than to North and South.